Where do they go? : a national review of current centrally funded treatment options for antisocial behaviours in New Zealand youth : a thesis presented in partial fulfilment of the requirements of the Masters in Public Policy at Massey University - Bergquist, Roy Leonard (Massey University, 2005)
Treatment of antisocial behaviour in adolescents is a matter for debate in this country. Many of the methods used historically, such as residential care, in general appear to be unsuccessful and have not helped the steady increase in numbers needing treatment. A paradigm shift away from the benefits of residential care and institutionalising is evident with the emergence of more family/community-based models of treatment. Maori and Pacific youth statistically are over-represented in this group of young people. Is this reflected in the type of treatment programmes available and is this client group being catered for culturally? This thesis looks at the options currently available nationally for the treatment of antisocial behaviours in youth. Where do they go, and what happens when they get there? New Zealand studies of treatment options currently available and their effectiveness are rare. This thesis interviews treatment providers nationally then discusses the themes and policy implications in focus groups in Auckland, Wellington and Christchurch. It is clearly shown that this group of young people are dealt with by a large number of sectors and organisations, often with a lack of a co-ordinated approach. Taking a phenomenological approach to the inquiry, the investigation utilised participant observation, semi-structured interviews and focus groups. The research is significant as it adds to research on 'intervention' in this field in Aotearoa New Zealand.
Keywords: New Zealand; Rehabilitation; Juvenile delinquents